การพัฒนาหลักสูตรส่งเสริมทักษะชีวิตโดยใช้โครงงานเป็นฐาน สำหรับนักเรียนชั้นประถมศึกษาปีที่ 5 - พงษ์ปรีชา ชฎารัตน์; สีทอง ปริญญภาษ (วารสารวิชาการศึกษาศาสตร์ ศรีนครินทรวิโรฒ, 2022)
บทคัดย่อ งานวิจัยนี้มีวัตถุประสงค์ เพื่อสร้างและหาประสิทธิผลของหลักสูตรส่งเสริมทักษะชีวิตโดยใช้โครงงานเป็นฐาน สำหรับนักเรียนชั้นประถมศึกษาปีที่ 5 และศึกษาผลการใช้หลักสูตรส่งเสริมทักษะชีวิตโดยใช้โครงงานเป็นฐานสำหรับนักเรียนชั้นประถมศึกษาปีที่ 5 กลุ่มตัวอย่าง ได้แก่ นักเรียนชั้นประถมศึกษาปีที่ 5/3 ภาคเรียนที่ 2 ปีการศึกษา 2563 โรงเรียนอนุบาลลำพูน จำนวน 40 คน ซึ่งได้มาจากการสุ่มกลุ่มตัวอย่างแบบกลุ่ม เครื่องมือที่ใช้ในการวิจัย ได้แก่ หลักสูตร คู่มือการใช้หลักสูตร และแบบวัดทักษะชีวิตด้านการจัดการกับอารมณ์และความเครียด วิเคราะห์ข้อมูลโดยใช้สถิติ ค่าเฉลี่ย ค่าร้อยละ ส่วนเบี่ยงเบนมาตรฐานและการทดสอบค่าที (t-test dependent) ผลงานวิจัยพบว่า 1) หลักสูตรส่งเสริมทักษะชีวิตโดยใช้โครงงานเป็นฐานสำหรับนักเรียนชั้นประถมศึกษาปีที่ 5 มีความเหมาะสมในภาพรวมอยู่ในระดับมาก และประสิทธิผลของการเรียนตามหลักสูตร เท่ากับ 0.7165 แสดงว่านักเรียนมีความก้าวหน้าทางการเรียนหลังเรียนสูงกว่าก่อนเรียนคิดเป็นร้อยละ 71.65 2) ผลการประเมินทักษะชีวิตด้านการจัดการกับอารมณ์และความเครียดโดยนักเรียนมีคะแนนเฉลี่ยทักษะชีวิตหลังเรียนสูงกว่าก่อนเรียนอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 และจากการประเมินทักษะชีวิตด้านการจัดการกับอารมณ์และความเครียดโดยผู้สอน นักเรียนมีคะแนนเฉลี่ยทักษะชีวิตหลังเรียนสูงกว่าก่อนเรียนอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 คำสำคัญ : การพัฒนาหลักสูตร, ทักษะชีวิต, โครงงานเป็นฐาน ABSTRACT The objective of this research is to create and seek for the effectiveness of life skill facilitation course by project based learning for 5th grade students. Then I studied the result of life skill facilitation course by project based learning for 5th grade students. The sampling used in the study are 40 of 5th grade students room 3 who were studied in the second semester of academic year 2020 at Anubanlamphun School. The sampling is approached by cluster random sampling. Tools used in this research consist of the manual for curriculum course and life skill test in emotional and stress management. Data was analysed by statistic, mean, percentage, standard deviation, and t-test dependent. According to the research, the findings are as follows: 1) The created course is life skill facilitation course by project based learning for 5th grade student The result of quality assessment ,by specialist, found that the course is very suitable as a whole picture and the efficacy of studying following the course is 0.7165 ,which is interpreted that students have improvement of studying by 71.65% after finishing the course. 2) The result of the evaluation of life skill specific in emotion and stress management, which was rated by students, found that they have a significantly higher average score after finishing the course, with a p-value of 0.05. Also, the result of the evaluation of life skill specific in emotion and stress management, which was rated by teachers, found that students have a significantly higher average score after finishing the course, with a p-value of .05. Keywords: Development of Course, Life Skill, Project Based Learning